Extraction of polyunsaturated fatty acids to reduce the iodine number of biodiesel products. Issue 1 (April 2020) - Helwani, Z; Umar, L; Neonufa, G F.; Puspawiningtyas, E; Prakoso, T; Lugito, G
Abstract: In the last ten years, Indonesia has succeeded in realizing the production and commercialization of oxygenated biofuel/bioethanol and bioethanol, even has applied mixing biodiesel into diesel to up to 20%-volume (or known as a B20 mixture). This success has at least helped reduce imports of fuel oil (BBM) such as diesel and gasoline, but no more than 20%. The rest (i.e., at least 80%) must still be imported and will cause severe pressure on the country's balance of payments because the current volume of fuel imports is no less than 50% of domestic needs. The quality of Indonesian biodiesel products generally still has a high cloud point and low oxidation stability. Diesel engine fuel consists of a mixture of methyl ester fatty acids (FAME: Fatty Acids Methyl Ester). Many constituent components are limited or not large (consist of 7-14 carbons). The essential constituents are the methyl esters of lauric, myristic, palmitic, stearic, oleic, linoleic, and linolenic acids. Methyl esters of polyunsaturated fatty acids (linoleic, linolenic, eleostearic) are inferior because they have a low cetane number and low oxidative stability. While methyl esters of saturated fatty acids have a superior demonic rate but have a high melting point (bad, higher than the requirements given by SNI). Related to the amount of unsaturated fat in biodiesel, it can reduce the quality of biodiesel, such as acid numbers, moisture content, and the emergence of sludge. Based on the current condition of biodiesel quality, to improve the quality of biodiesel produced can be done by reducing the number of unsaturated fats present in the biodiesel product. The initial step that has to be done is separation biodiesel products into saturated biodiesel with the characteristic iodine number <30-40 and unsaturated biodiesel with an iodine number > 70 through a fractionation process. Extraction was carried out using AgNO3 with variations in the ratio of biodiesel feed to solvents. The best ratio of biodiesel:AgNO3 to eliminate the levels of polyunsaturated free fatty acids in biodiesel products is 1:2 with an iodine value of 47.38 gr I2 /(100 gr oil)